Dynamika liczebności niedźwiedzia brunatnego w Karpatach Wschodnich - Khoyetskyy, Pavlo (Leśne Prace Badawcze, 2013)
There have been two periods of change in the dynamics of bear population in the Eastern Carpathians. The first period lasted over 50 years, starting in the late 1940s and ending in the year 2001. The second period started in the early 21st century. The bear population reached its maximum- of about 1100 individuals – in the early 1970s. Over 85% of recorded bear deaths have resulted from poaching.